A level set based topology optimization for elastodynamic problems using BEM - Li, Huiwen; Gao, Haifeng; Liang, Jianguo; Li, Zhiqiang; Xu, Huidong; Zheng, Changjun (Frontiers in Physics, 2024)
The paper presents a topology optimization methodology for 2D elastodynamic problem using the boundary element method(BEM). The topological derivative is derived basing on the variation method and the adjoint variable method. The level set method is employed for representation of the material domain and voids in a specified design domain. Thus the generation of the boundaries can easily follows the zero isocontour of the level set function. Numerical implementation is carried out to demonstrate the effectiveness of the proposed topology optimization methodology in wave isolation and waveguide problems.